2007
DOI: 10.1029/2006ja011940
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the force‐free model of magnetic clouds for their heliospheric evolution

Abstract: [1] We examine the implications of the widely used, force-free, constant-a flux rope model of interplanetary magnetic clouds for the evolution of these mesoscale (fraction 1 AU) structures in the heliosphere, with special emphasis on the inner ( 1 AU) heliosphere. We employ primarily events observed by the Helios 1 and 2 probes between 0.3 and 1 AU in the ascending and maximum phases of solar cycle 21 and by Wind at 1 AU in a similar phase of solar activity cycle. We supplement these data by observations from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
164
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(212 citation statements)
references
References 41 publications
43
164
4
1
Order By: Relevance
“…These two similar studies have surprisingly different exponents for the power law fits (Table 2). Our result best agree with Wang et al (2005), who found the same exponent as Leitner et al (2007).…”
Section: Comparison To Previous Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…These two similar studies have surprisingly different exponents for the power law fits (Table 2). Our result best agree with Wang et al (2005), who found the same exponent as Leitner et al (2007).…”
Section: Comparison To Previous Studiessupporting
confidence: 82%
“…Our exponent is closer to the results of Leitner et al (2007) within the inner heliosphere (while for the diameter, the agreement is best for the full range of D, Table 2). Our results are also compatible with both ICME studies within the uncertainties of the exponents (however, we do not compute a mean field, as for ICME studies).…”
Section: Comparison To Previous Studiessupporting
confidence: 61%
See 1 more Smart Citation
“…Such radial evolution is otherwise available only from a statistic analysis of a large number of MCs observed individually at various distances (Liu et al 2005;Wang et al 2005a;Leitner et al 2007;Gulisano et al 2010), with possible bias coming from the selection of MCs with different properties. Another application of line-up spacecraft is to derive the evolution of global magnetohydrodynamic (MHD) quantities, such as magnetic flux and magnetic helicity (Dasso 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The simplest solution is obtained with a cylindrical boundary; this is the so-called Lundquist model (Lundquist 1950). It was, and is still, widely used to fit the magnetic field observed in MCs and to derive global quantities such as the magnetic flux and helicity (e.g., Burlaga 1988;Lepping et al 1990;Dasso et al 2003;Lynch et al 2003;Dasso et al 2005b;Mandrini et al 2005;Dasso et al 2006;Leitner et al 2007). An extension of this model to an elliptical boundary was realized by Vandas & Romashets (2003).…”
Section: Introductionmentioning
confidence: 99%